PENGGUNAAN REGISTER DALAM HALAMAN KONTES KECANTIKAN DI MEDIA SOSIAL INSTAGRAM - MALENSANG, TRIA DIVINITY; LOTULUNG, DONALD R.; WANTASEN, ISNAWATI LYDIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT This research entitled â€˜Register Used in Beauty Pageants Page of Social Media Instagramâ€™. It is expected to give contribution for the theoretical building of the linguistic field, particularly supports the development of subject dealing with sociolinguistics for the other studies and especially also for the beauty pageants lover as this research about the register used in beauty pageants page of media social Instagram. It is an attempt to identify and classify the register used in beauty pageants page in social media instagram and to analyze the variation of language and linguistic form of register used in beauty pageants page in social media instagram. The theories which used in this research are Martin Joos (1968) about variation of language and George Yule (2006) about linguistic form and this research applies a descriptive method. Data were taken in instagram posting from January 2016 to July 2018 posted by 21 users who have been followed by the writer. The result shows that register found in instagram are pride, winner, gown, wardrobe, top, sneakpeak, beauty class, close up battle, catwalk class, bubbling up, placed, styled, crowned, brushed, cocktail dress, stunning, beauty queen, miss, yash, sist, shay, missosology, muses, sash, backtoback, backstage, wishlist, fasttrack, grandfinal, hotpick, funfact, photoshoot, titleholder, powerhouse, firstwalk, glamshoot, fitting, photo, asst, decor, pic, represent, roat to, opnum, MUA, PL, MGIO, BWAP, QNA, BTS, MUO, MS, RU, natcos and TBA. Variation of language that used in register word in instagram are frozen, formal, consultative, casual and intimate, while linguistic form of register found in Instagram are coinage, borrowing, compounding, blending, clipping, backformation, conversion and acronyms. The meanings ofÂ register found using an online dictionary.Keywords : Register, Instagram: Beauty Pageants, Sociolinguistic Analysis